2022
DOI: 10.1111/are.15890
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic effects of the fungi,Aspergillus nigeron growth, immunity, haematology, intestine fungal load and digestive enzymes of the common carp,Cyprinus carpio

Abstract: The present study was conducted to investigate the probiotic role of the unicellular fungi, Aspergillus niger on growth performance, immunity, haematology and digestive enzymes in common carp, Cyprinus carpio. One non‐supplemented group (T0) was considered as control and two groups fed the fungi including T1 (fish supplemented with diet containing 1 × 103 A. niger) and T2 (fish supplemented with diet containing 1 × 106 A. niger) considered as the experimental treatments in three replicates. Fish were fed exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 85 publications
2
7
0
Order By: Relevance
“…Results showed that the inclusion of A. niger can enhance the weight gain, specific growth rate, and length gain of shrimps, especially in the A1.5, indicating the growth promotion of A. niger (at 1.5 g/kg diet) shrimps under culture conditions. This similar to the previous findings in common carp fed a diet supplemented with A. niger (at 1×10 3 or 1×10 6 CFU/g diet) (Jasim et al, 2022). Jasim et al (2022) showed an improvement in the final length and weight, weight gain, thermal growth coefficient, protein efficiency ratio, lipid efficiency ratio, feed conversion ratio, immune response, and activity of digestive enzymes of fish fed with diets supplemented with A. niger.…”
Section: Sharma Et Al (2022) Indicated Thatsupporting
confidence: 90%
See 4 more Smart Citations
“…Results showed that the inclusion of A. niger can enhance the weight gain, specific growth rate, and length gain of shrimps, especially in the A1.5, indicating the growth promotion of A. niger (at 1.5 g/kg diet) shrimps under culture conditions. This similar to the previous findings in common carp fed a diet supplemented with A. niger (at 1×10 3 or 1×10 6 CFU/g diet) (Jasim et al, 2022). Jasim et al (2022) showed an improvement in the final length and weight, weight gain, thermal growth coefficient, protein efficiency ratio, lipid efficiency ratio, feed conversion ratio, immune response, and activity of digestive enzymes of fish fed with diets supplemented with A. niger.…”
Section: Sharma Et Al (2022) Indicated Thatsupporting
confidence: 90%
“…This similar to the previous findings in common carp fed a diet supplemented with A. niger (at 1×10 3 or 1×10 6 CFU/g diet) (Jasim et al, 2022). Jasim et al (2022) showed an improvement in the final length and weight, weight gain, thermal growth coefficient, protein efficiency ratio, lipid efficiency ratio, feed conversion ratio, immune response, and activity of digestive enzymes of fish fed with diets supplemented with A. niger. Also, in another study, supplementation of Aspergillus oryzae singly or in combination with b-glucan can increase the growth, feed efficiency, antioxidant status, and immunomodulation of Nile tilapia (Dawood et al, 2020).…”
Section: Sharma Et Al (2022) Indicated Thatsupporting
confidence: 90%
See 3 more Smart Citations